Administrative decentralization policies and developments in educational quality management in Peru - Mayta Huiza, Dora Amalia; Jinchuña Huallpa, Jorge; Chambi Palero, Asunción; Flores Arocutipa, Javier Pedro; Luján Minaya, Julio César (Frontiers in Education, 2025)
The objective of the research was to determine the relationship between decentralized policies, techniques, and human resources directly related to improving educational quality and the influence of supervisory actions and information and communication technologies in the Local Educational Management Unit of Puno, Peru, 2023. It is quantitative in approach, non-experimental in design, and causal explanatory, with a sample of 203 collaborators who were given a questionnaire. The analysis was performed using SEM-PLS. The findings reveal that the implementation of administrative management decentralization policies is still too weak to achieve educational quality (R2 = 0.034), while the impact of the mediating variables of supervision and the use of information and communication technologies is very significant and strong (f2 > 0.35) in the direct relationship between decentralized management policies and educational quality management. It is concluded that ongoing supervision and the implementation of information and communication technologies are important for improving educational quality management and administrative activities.